The making of the Prime Minister H.S. Suhrawardy in an anagram polity, 1947-1958 - Harun, Shamsul Huda.; Institute of Liberation Bangabandhu and Bangladesh Studies (Dhaka : Institute of Liberation Bangabandhu and Bangladesh Studies, National University, 2001)
Political development in Pakistan that led Huseyn Shaheed Suhrawardy, 1892-1963, to become the prime minister.
Includes bibliographical references and index.
Keywords: Suhrawardy, Huseyn Shaheed, -- 1892-1963.; Pakistan -- Politics and government